Problems Faced by Students and Teachers during Online Classes in Chennai - A, Bifi Simon; Selvakumar, Y Stanly (Journal of Advanced Research in English & Education; Vol 7 No 2 (2022): Journal of Advanced Research in English and Education, 2022)
The COVID-19 pandemic has created a massive changes in education sector all over the world. As schools were forced to shut down, there was a major disruption in teaching and in learning techniques, so here we will analyze the problems faced by students and teachers during online classes in Chennai by, How the technology was used to continue their education in both teaching and in learning, the major issues faced by students in the usage of mobile phones, the difficulty of the teacher to teach effectively and so on. How to cite this article:  Simon AB, Selvakumar YS. Problems Faced by Students and Teachers during Online Classes in Chennai. J Adv Res Eng & Edu 2022; 7(2): 5-7. DOI:  https://doi.org/10.24321/2456.4370.202202